Impact of crime victimization on initial presentation to an early intervention for psychosis service and 18‐month outcomes. Issue 2 (13th January 2015) - Fisher, Helen L.; Roberts, Anna; Day, Fern; Reynolds, Nicky; Iacoponi, Eduardo; Garety, Philippa A.; Craig, Thomas K.J.; McGuire, Philip; Valmaggia, Lucia; Power, Paddy
Abstract: Aim: To investigate the clinical and social correlates of a lifetime history of crime victimization among first‐episode psychosis patients at entry to an Early Intervention Service and following 18 months of specialist care. Methods: Face‐to‐face interviews were conducted with 149 individuals who presented to an Early Intervention Service for the first time with psychosis in the London borough of Lambeth, UK. A range of demographic and clinical measures were completed including self‐reported history of victimization along with the type of crime and its subjective effect on the patient. Clinical and functional outcomes at 18‐month follow up were ascertained from clinical case notes by a psychiatrist. Results: A large proportion of patients ( n = 64, 43%) reported a history of crime victimization. This was associated with significantly higher levels of depression and substance misuse at initial presentation. Being a victim of a crime was not significantly associated with poorer clinical or functional outcomes after 18 months of specialist care. However, non‐significant differences were found for those who reported crime victimization in terms of their increased use of illegal substances or having assaulted someone else during the follow‐up period. Conclusion: Past experience of being a victim of crime appears to be common in patients presenting for the first time with psychosis and is associated with increased likelihood of comorbidity. Thus, Early Intervention Services should consider screening for past victimization and be prepared to deal with comorbid problems. The impact of crime victimization on clinical and functional outcomes requires investigation over a longer period of time.